Religious, Socio-cultural and Political Worldviews of Contemporary Pagans in the Czech Republic - Vencálek, Matouš (Pomegranate, 2018)
This paper presents the results of a research inspired by Helen Berger’s Pagan Census, conducted among Czech Pagans. It explores the worldviews of Czech Pagans from different Pagan groups regarding the questions of spirituality (e.g. the beliefs about afterlife, reincarnation or magic), society and culture (e.g. LGBTQ+ rights, drugs or the status of women in society) and politics (e.g. regarding the market regulation, social welfare, as well as specific political party preferences). It focuses on the differences, as well as on the commonalities among various Pagan groups, as the Pagan movement is highly diversified and sprouts from several different sources: some groups have emerged from naturalizing and romanticizing tendencies and emphasize the sacredness of nature, worship, and respect for all of its creatures; while some groups have emerged from rather nationalistic tendencies and focus on the worship of the gods and ancestors with a strong emphasis on ethnic background. The results show that the vast majority of Czech Pagans believe in some sort of afterlife and more than a half of them believe in reincarnation. The vast majority also believe in magic and nearly a half of them practice it. While there are little differences between various Pagan groups on the left-right economic scale, as they all seem to be mostly centrist or slightly left of center, adherents of reconstructionist or ethnic Pagan groups tend to hold more conservative positions on the socio-cultural scale than the adherents of revivalist or eclectic Pagan groups.